Citizens and the state in authoritarian regimes comparing China and Russia - Koesel, Karrie J. 1974-; Bunce, Valerie 1949-; Weiss, Jessica Chen (Oxford University Press, 2020)
"This volume compares the most powerful authoritarian states in global politics today: Russia and China. For all their power and money, both regimes have faced difficult tradeoffs in seeking both political stability and reliable information about society while confronting the West and its international influence. They have also made different choices: Russia today is a competitive authoritarian regime, while China is a non-competitive authoritarian regime. Desite the different paths taken after the tumultuous events of 1989, both regimes have returned to a more personalized form of authoritarian rule. By placing China and Russia side-by-side, this volume examines regime-society relations and produces new insights, including what strategies their rulers have used to stay in power while forging political stability and gathering information; how societal groups have resisted, complied, or responded to these strategies; and what costs and benefits, anticipated and unexpected, have accompanied the bargains political leaders and their societies have struck. The essays in this volume change the way we understand authoritarian politics and expand the terrain of how we analyze regime-society relations in authoritarian states. On the societal side, this book looks not just at society as a whole, but also the more specific roles of public opinion, labor politics, political socialization, political protests, media politics, environmental movements, and non-governmental organizations. On the regime side, this study is distinctive in examining not just domestic threats and the general strategies rulers deploy in order to manage them, but also international threats and the rationale behind and impact of new laws and new policies, both domestic and international"--
Keywords: Medien; Gesellschaft; Autoritärer Staat; China; Russland; Political participation / China; Political participation / Russia (Federation); Political stability / China; Political stability / Russia (Federation); Authoritarianism / China; Authoritarianism / Russia (Federation); China / Politics and government / 2002-; Russia (Federation) / Politics and government / 1991-; Authoritarianism; Political participation; Political stability; Politics and government; Russia (Federation); Since 1991; Aufsatzsammlung